The cyclin dependent kinase inhibitor p21Cip1/Waf1 is a therapeutic target in high-risk neuroblastoma - Sorteberg, Agnes Luise; Halipi, Vesa; Wickström, Malin; Shirazi Fard, Shahrzad (Frontiers in Oncology, 2022)
Platinum-based chemotherapies such as cisplatin are used as first-line treatment for the paediatric tumour neuroblastoma. Although the majority of neuroblastoma tumours respond to therapy, there is a high fraction of high-risk neuroblastoma patients that eventually relapse with increased resistance. Here, we show that one key determinant of cisplatin sensitivity is phosphorylation of the cyclin-dependent kinase inhibitor p21Cip1/Waf1. A panel of eight neuroblastoma cell lines and a TH-MYCN mouse model were investigated for the expression of p21Cip1/Waf1 using RT-qPCR, Western blot, and immunofluorescence. This was followed by investigation of sensitivity towards cisplatin and the p21Cip1/Waf1 inhibitor UC2288. Whereas the cell lines and the mouse model showed low levels of un-phosphorylated p21Cip1/Waf1, the phosphorylated p21Cip1/Waf1 (Thr145) was highly expressed, which in the cell lines correlated to cisplatin resistance. Furthermore, the neuroblastoma cell lines showed high sensitivity to UC2288, and combination treatment with cisplatin resulted in considerably decreased cell viability and delay in regrowth in the two most resistant cell lines, SK-N-DZ and BE(2)-C. Thus, targeting p21Cip1/Waf1 can offer new treatment strategies and subsequently lead to the design of more efficient combination treatments for high-risk neuroblastoma.